Keterampilan Konselor Berbasis Budaya - Nidya Roza; Silvianetri .; Wahidah Fitriani (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2022)
The skills that must be possessed by a counselor are not only basic skills in understanding techniques to carry out various counseling services. However, a great counselor must also master and know the various values ​​that live in society, even though these values ​​are different from the values ​​they hold. It is possible that a counselor will deal with clients from different cultural backgrounds. This article was written with the aim of describing the cultural-based counseling skills that should be held by a counselor, especially counselors who are in a culturally diverse society. This article uses library research methods and literature studies by analyzing various interesting studies that give rise to new theories that can be seen logically to become something that can be applied in the field. Improving the skills of the counselor does not need to be by eliminating or removing the basic skills that the counselor already has. Even the various abilities that counselors already have can be used by utilizing and devoting these strengths to the fullest. Keywords: counselor skills; culture-based counseling